2008
DOI: 10.1007/s00132-008-1237-1
|View full text |Cite
|
Sign up to set email alerts
|

Sonographisches Hüftscreening in Deutschland

Abstract: General ultrasound screening programmes to determine DDH are still a matter of discussion due to a lack of evidence. To facilitate further discussions this review gives an overview of the international data and literature concerning the different screening policies taking into account the results of the German evaluation study from 1997 to 2002. General ultrasound screening programmes are established in Germany and Austria. The analysis of the German screening showed 535 cases of DDH with first operative proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Universal US screening has been in place in Germany since 1996. The German language literature supports this position, in terms of reduced late diagnosis and reduced rates of late surgery related to dysplasia [61,63,92].…”
Section: Selective Vs Universal Us Screeningmentioning
confidence: 78%
See 1 more Smart Citation
“…Universal US screening has been in place in Germany since 1996. The German language literature supports this position, in terms of reduced late diagnosis and reduced rates of late surgery related to dysplasia [61,63,92].…”
Section: Selective Vs Universal Us Screeningmentioning
confidence: 78%
“…The German language literature supports this position. Ihme et al [92] compared the costs of hip surgery due to DDH at two different time periods (patients who received US and a historical group) and demonstrated that the costs of hip US were lower than the costs of hip surgery. This position was further supported by the study by Farr [65].…”
Section: Selective Vs Universal Us Screeningmentioning
confidence: 99%
“…The Australian screening programme relies more on clinical examination and the Austrian and German programmes involve a universal USS. 5 The lack of a universal definition of DDH makes it difficult to ascertain an exact incidence, however, in the United States it is believed to be around 1 in 1000 live births. 6 In the United Kingdom, the incidence of DDH diagnosed late, that is, above 1 year old, was calculated at 1.28 per 1000 births despite the selective USS screening programme.…”
mentioning
confidence: 99%
“…Two to three-year-old children often undergo nonsurgical treatment, with a closed reduction after the use of frog-shaped gypsum or fixation of subbranches. Some countries such as Germany have universal screening programmes and have seen a decrease in the rates of surgical reduction in DDH[ 6 ]. Patients over 3 years old are treated by surgery.…”
Section: Discussionmentioning
confidence: 99%